Triple Helix Theory: What does the research of the Brazilian Postgraduate Programs present? (Research, Society and Development, 2021)
The study carried out a systematic review of research in Brazilian Postgraduate Programs on the Triple Helix theory. The database used was the catalog of Brazilian dissertations and theses, available on the CAPES Sucupira Platform. All academic productions on the Triple Helix, referenced in the Brazilian catalog, were admitted. The main results of the research showed the existence of little institutional relationship and joint strategic forms in Brazilian decision-making. The number of Brazilian productions on the Triple Helix is incipient (169 scientific works), considering the period 1995-2021. The largest volume of production on the subject is in the Postgraduate Programs in Administration and the state with the highest number of defended researches was Catherine Saint. Based on the Triple Helix, the main needs diagnosed in the research were: To make efforts to establish and systematize synergistic relationships between institutional agents; Structuring interaction networks for assertive decision making; Apply sustainable performance indicators to institutional development; Favor planned behavioral bonds between knowledge agents; Structuring strategic systems for national development.